Morroniside attenuates nucleus pulposus cell senescence to alleviate intervertebral disc degeneration via inhibiting ROS-Hippo-p53 pathway - Zhou, Chengcong; Yao, Sai; Fu, Fangda; Bian, Yishan; Zhang, Zhiguo; Zhang, Huihao; Luo, Huan; Ge, Yuying; Chen, Yuying; Ji, Weifeng; Tian, Kun; Yue, Ming; et al. (Frontiers in Pharmacology, 2022)
Intervertebral disc (IVD) degeneration (IVDD) which is highly prevalent within the elderly population, is a leading cause of chronic low back pain and disability. Nucleus pulposus (NP) cell senescence plays an indispensable role in the pathogenesis of IVDD. Morroniside is a major iridoid glycoside and one of the quality control metrics of Cornus officinalis Siebold & Zucc (CO). An increasing body of evidence suggests that morroniside and CO-containing formulae share many similar biological effects, including anti-inflammatory, anti-oxidative, and anti-apoptotic properties. In a previous study, we reported that Liuwei Dihuang Decoction, a CO-containing formula, is effective for treating IVDD by targeting p53 expression; however, the therapeutic role of morroniside on IVDD remains obscure. In this study, we assessed the pharmacological effects of morroniside on NP cell senescence and IVDD pathogenesis using a lumbar spine instability surgery-induced mouse IVDD model and an in vitro H2O2-induced NP cell senescence model. Our results demonstrated that morroniside administration could significantly ameliorate mouse IVDD progression, concomitant with substantial improvement in extracellular matrix metabolism and histological grading score. Importantly, in vivo and in vitro experiments revealed that morroniside could significantly reduce the increase in SA-β-gal activities and the expression of p53 and p21, which are the most widely used indicators of senescence. Mechanistically, morroniside suppressed ROS-induced aberrant activation of Hippo signaling by inhibiting Mst1/2 and Lats1/2 phosphorylation and reversing Yap/Taz reduction, whereas blockade of Hippo signaling by Yap/Taz inhibitor-1 or Yap/Taz siRNAs could antagonize the anti-senescence effect of morroniside on H2O2-induced NP cell senescence model by increasing p53 expression and activity. Moreover, the inhibition of Hippo signaling in the IVD tissues by morroniside was further verified in mouse IVDD model. Taken together, our findings suggest that morroniside protects against NP cell senescence to alleviate IVDD progression by inhibiting the ROS-Hippo-p53 pathway, providing a potential novel therapeutic approach for IVDD.